Does risk-based decision-making present an 'epistemic trap' for climate change policymaking?. (1st November 2020) - Tangney, Peter
Abstract : Risk-based decision-making is widely considered to be the best means of presenting the science of climate change and for developing and presenting climate change evidence for policymaking. This paper examines some of the justifications provided by climate and decision scientists for their preferred approach, and argues that, although risk-based approaches are indeed analytically and instrumentally helpful, they may not always provide the most politically appropriate framework for resolving the politics of evidence-based policymaking. Decision scientists still promote risk-based decision-making under erroneous ideals of linear-instrumental-rationality, even if they have become more circumspect concerning the worst excesses of past technocratic linear-rationality. Moreover, decision scientists have provided very shallow justification to date for 'risk' as default decision framework. A reasonable analysis of the general suitability of risk would include comparative analysis with alternative conceptual frames, not simply in terms of their analytical power, but also their political acceptability in constituencies where particular evidence-frames may be challenged on the basis of their premises, rather than their conclusions.